Community empowerment in acculturating PHBS and family food gardens in Tambakbaya Village, Lebak Regency - ahmad, ahmad (Jurnal Menara Pengabmas, 2024)
Healthy and Clean-Living Behavior (PHBS) is a social engineering that aims to make as many community members as possible as agents of change in order to improve the quality of daily behavior with the aim of living clean and healthy. The household environment is one of the settings where PHBS can be practiced. PHBS in Households is an effort to empower household members to know, want and be able to practice clean and healthy living behaviors and play an active role in the health movement in the community. Health cemter data and information from the Tambakbaya village midwife show that there are several health problems in the village, including poor environmental health, community behavior that is detrimental to their health such as the discovery of adolescents who smoke, there are still many young women who have early marriages and the occurrence of anemia in adolescents and the discovery of 131 cases of stunting in 2022. This number is the highest case of 9 villages in the Mandala Health Center working area. The high number of stunting cases encourages us to try to understand the causes and look for handling and control efforts that can be carried out by the community. Community service carried out with the Partner Village Development Program (PPDM) scheme through community empowerment activities in practicing PHBS in households and making "Family Food Gardens" as an effort to meet family food needs to prevent and control the incidence of stunting in the community. The targets of the activity are village health supervisors, village officials, health cadres, and community groups in Tambakbaya Village, Cibadak District, Lebak Regency. Community service activities carried out in the form of training health cadres and families with stunting cases who have the readiness to build "Family Food Gardens" as a model in optimizing home yard land, to support the fulfillment of their family's vegetable needs. The results of community service activities are increasing the knowledge of the Tambakbaya village community about Clean and Healthy Living Behavior, and stunting, the construction of a hand washing station at the Tambakbaya village office as a model in forming a culture of clean and healthy living in the community and the construction of 15 pilot models of stunting family food garden development by utilizing the home environment of stunting families.